Educação de Jovens e Adultos : as ações do MOBRAL no Município de Patos de Minas/MG (1970-1980) - Coelho, Leni Rodrigues (2008)
This search aims to analyse the ideas, the implantation process and the Movimento Brasileiro de Alfabetização (MOBRAL) Literacy State Progam and its pedagogical practices in Patos de Minas, MG between 1970-1980. This subject is relevant to the academic area because it discusses a problem left in secundary plans by governments, once the developed actions in this area had not overcomed the illiteracy problems. MOBRAL, a program reserved for youth and adults education was founded in december 15th/1967 by the law n. 5,379, however, it has been stablished in Patos de Minas city almost three years later, in september 17th/1970. Among the sources of this study, officials documents, oral history (former-superviser, formerteachers and alumni interviews), the 1970 and 1980 statistics tables from IBGE, the pedagogical manuals and also the local press will all be emphasized. This program was one of the most important politic educacional faces of the military dictation period, and its concepcion comprehend the education as labor force qualification. It also aimed to integrate the illiteracy mass to the capitalist system. Otherwise, principles such as mass participation would not prevail, since it could lead to social changes when the government mattered was to moderate the democratics interess. MOBRAL was a project with a main ideological and politcal stamp, although the government planned it to be simply a literacy tool. In this sense, the democratics interess had not been privileged in favour those illiterats.